Handbook of Freemasonry - Bogdan, Henrik.; Snoek, Joannes Augustinus Maria, 1946- (Brill Handbooks on Contemporary Religion, 2014)
Freemasonry is the largest, oldest, and most influential secret society in the world. The Brill Handbook of Freemasonry is a pioneering work that brings together, for the first time, leading scholars on Freemasonry. The first section covers historical perspectives, such as the origins and early history of Freemasonry. The second deals with the relationship between Freemasonry and specific religious traditions such as the Catholic Church, Judaism, and Islam. In the third section, organisational themes, such as the use of rituals, are explored, while the fourth section deals with issues related to society and politics - women, blacks, colonialism, nationalism, and war. The fifth and final section is devoted to Freemasonry and culture, including music, literature, modern art, architecture and material culture.